농지보전과 농업진흥지역제도 개선방안 - 김수석 (한국농촌경제연구원, 2009)
As people are more worried about food security, farmland preservation is drawing more attention from the government as well as the public. According to a recent survey on social consciousness, about 80% of people point out the significance of preserving the farmland. However, the current system to preserve the farmland has several limitations due to such factors as the ambiguity of the term "necessary acreage of farmland" to secure food supply. To make it worse, the recent abolition of a scheme to designate alternative farmland makes it more challenging to keep the necessary acreage for farming. The reformation of the farmland preservation system has to be directed in a way that secures an essential acreage of farmland. We need to restrict the usage of land so that it can not be used for purposes other than agricultural activity in rural development regions. When it is diverted to other purposes, a certain portion of the loss should be made up with a new farmland, possibly from land reclamation. To prevent the development made without any thoughts to the environment, we are proposing to designate a district called “common facility district” where all the facilities not related with agricultural production will be constructed in a designated area. It is necessary to modify the system such that the government levies heavy penalties for diverting the preservation farmland to other purposes and compensates the loss that may be incurred when the diversion of farmland into more profitable industrial or residential land is prevented.
Keywords: 농지보전; 농지정책